2003
DOI: 10.1002/pola.10979
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular poly(ether ketone)–polyisobutylene pseudo‐block copolymers

Abstract: The association behavior of telechelic hydrogen‐bonded poly(ether ketone) (PEK) and polyisobutylene (PIB) polymers and the formation of a new class of pseudo‐block copolymers is reported. The attachment of complementing hydrogen bonds (thymine/2,6‐diaminotriazine and cytosine/2,6‐diaminotriazine) onto the respective PIB and PEK polymers leads to a dramatic increase in the miscibility between the normally immiscible PEK and PIB polymers. The structure formation in the liquid state was studied by dynamic NMR spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 48 publications
0
54
0
1
Order By: Relevance
“…Such a material requires immiscible polymeric components, in which macrophase separation is prevented by strong and complementary noncovalent bonds between the telechelic blocks. Telechelic polymers with multiple H-bonding endgroups have been prepared by means of postpolymerization modification routes (14)(15)(16)(17)(18)(19)(20)(21)(22). However, incomplete reaction leads to small, yet detrimental, amounts of monofunctionalized polymers, which act as chain stoppers.…”
mentioning
confidence: 99%
“…Such a material requires immiscible polymeric components, in which macrophase separation is prevented by strong and complementary noncovalent bonds between the telechelic blocks. Telechelic polymers with multiple H-bonding endgroups have been prepared by means of postpolymerization modification routes (14)(15)(16)(17)(18)(19)(20)(21)(22). However, incomplete reaction leads to small, yet detrimental, amounts of monofunctionalized polymers, which act as chain stoppers.…”
mentioning
confidence: 99%
“…The polymers themselves often have broad molecular weight distributions or high T g s, necessitating melt annealing at temperatures high enough to significantly reduce the strength of the hydrogen bond. Despite these limitations, the incorporation of both homocomplementary 3,4,6,19 and heterocomplementary 14,16,[20][21][22][23][24] MHB groups at polymer chain ends has been previously demonstrated. In particular, the work of Mather et al 21 first demonstrated the incorporation of MHB chain ends through the use of controlled radical polymerization from uracilfunctional nitroxide initiators.…”
Section: Introductionmentioning
confidence: 99%
“…19 The nature of the interaction varies widely and most commonly consists of either metal-ligand, 20,21 ionic, 22,23 or hydrogen bonding. 24,25 Incorporation of these into various macromolecular architectures such as diblock, [26][27][28][29][30][31][32][33][34][35] triblock, [36][37][38] multiblock, [39][40][41] star 42 and graft copolymers, [43][44][45] blends, 35,46 and gels 47,48 has resulted in remarkably simple thermal control over the polymer structure and related properties.…”
Section: Introductionmentioning
confidence: 99%